Kali macrura Parr 1933 - Melo, Marcelo R. S. (Zenodo, 2008)
Kali macrura (Parr 1933) (Figs. 1 D, 6, and 7; Tables 1, 7, and 8) Hemicyclodon macrurus Parr 1933 [original description; type locality, off Acklins Islands, Bahamas, 22 ° 31 ’ 15 ” N, 74 ° 26 ’ 20 ” W, 10000 ft. (3048 m) of wire, 30 –III– 1927, R/V Pawnee holotype YPM 2739]. Kali macrurus Johnson 1969: 589, figure 1 [revision of the genus and key to the species]. Kali macrura Johnson and Cohen 1974: 39 –41 [revision of the genus, diagnosis and brief description]; Johnson and Keene 1986: 733 –734, figure 228.7 [key to the species]; Johnson and Keene 1990: 902 [record of eastern tropical Atlantic species]; McEachran and Sutton 2003: 1742 –1743 [list of Atlantic species]; Moore et al. 2003: 227 [checklist of deep-sea fishes from off New England, Western North Atlantic]; Hardy 2005: 1912 [identification of larvae]; Hardy 2007: 1902 [identification of larvae]; Smith (in press) [key to species]. Material examined. 26 specimens, including holotype. Atlantic, Slope Water: MCZ 165931, 1, 118.03 mm, 39 ° 47 ’ N, 66 ° 55 ’ W, 0–2208 m, 18 –VI– 2006, R/V Delaware II. Florida Straits: YMP 2739, holotype, 114.3 mm, 22 ° 31 ’ N, 74 ° 26 ’ W, 30 –III– 1927, R/V Pawnee UF 146164, 1, 112.3 mm, 2450 m, 24 –VII– 1971, R/V Pillsbury . Amazonian Province: MCZ 60723, 1, 72.5 mm, 9 ° 21 ’ N, 43 °09’ W, 2500 m, 27 –VII– 1983, R/V Columbus Iselin . South Atlantic Subtropical: SIO 63–542 –60, 1 113.8 mm, 31 °09.0’ S, 00° 45.5 ’ E, 0–2200 m, 9 –VI– 1963, R/V Argo UW 21247, 1, 117.0 mm (cs), 27 ° 14 ’ S, 2 ° 56 ’ W, 1900–2000 m, 1 –IV– 1971, R/V Walther Herwig . Guinean Province: USNM 207615, 1, 101.8 mm, 15 ° 45 ’ S, 6 °06’ W, 0–1900 m, 5 –VI– 1971, R/V Walther Herwig . Indian: USMN 207608, 1, 111.3 mm, 24 °03’ S, 65 °00’ E, 3500 m, 25 –VI– 1964, R/V Anton Bruun BMNH 1988.2.25.7–8, 2, 125.5 – 130.4 mm, 31 ° 55 ’ S, 55 °06’ E, 0–930 m, 29 –IV– 1936, R.R.S. Discovery II . Eastern Pacific: LACM 30428, 1, 105.5 mm, 33 °00’ N, 119 °00’ W [coordinates inferred], 17 / 18 –III– 1969, R/V Ve le ro LACM 30040 –11, 1, 121.4 mm, 22 °00’ N, 107 °00’ W [coordinates inferred], 12 –XI– 1967, R/V Vel ero Pacific, Pacific Plate: SIO 60–232 –60, 1, 108.9 mm, 04° 59 ’ S, 135 ° 19 ’ W, 0–2750 m, 1 –VII– 1960, R/V Spencer Baird SIO 60–229 –60, 1 100.0 mm, 01° 39 ’S, 133 ° 35.7 ’ W, 0–2326 m, 29 –VII– 1960, R/V Spencer Baird SIO 60–239 –60, 6, 87.9–115.3 mm, 05° 12 ’ N, 143 °07’ W, 0–2500 m, 6 –VII– 1960, R/V Spencer Baird SIO 60–219 –60, 2, 110.6 – 116.9 mm, 04° 42 ’N, 130 ° 50 ’ W, 0–2160 m, 26 / 27 –VI– 1960, R/V Spencer Baird USNM 207613, 1, 109.3 mm, 8 °00’ N, 164 ° 33 ’ W, 0–1400 m, 8 –VIII– 1963, R/V Te Vega ZMUC P. 6526, 1, 94.7 mm, 30 °08’ S, 176 ° 50 ’ W, 14 –XII– 1928, R/V Dana ZMUC P. 6525, 1, 87.6 mm, collected with ZMUC P. 6526. Diagnosis. Kali macrura is diagnosed from its congeners by two unique characteristic: the low number of total vertebrae, 33–34 ( vs. 37 or more); and by teeth in lateral series of premaxilla and dentary six to 10, needle-like at anterior fourth/third, respectively, followed by seven to 10 recurved teeth with ventral attachment in the posterior dentigerous area ( vs. teeth in lateral series of premaxilla of premaxilla and dentary recurved or caniniform in K. colubrina , K. falx , K. indica 12–31, needle-like, extending to the end of dentigerous area in K. kerberti and K. macrodon 18–32, recurved, with ventral attachment, extending to the end of dentigerous area in K. parri ). Kali macrura further differs from all species of Kali , except Kali parri by a smaller number of first dorsalfin rays, IX–XI, modally IX ( vs. first dorsal-fin rays XI or more); smaller number of second dorsal-fin rays, 18–21, modally 21 ( vs. second dorsal-fin rays usually 22 or more); anal-fin rays 19–21, modally 20 ( vs. analfin rays usually more than 22). Description. Smallest species of Kali , largest specimen examined 130.4 mm SL. Meristic data summarized in table 2, and morphometric in table 4. General body pattern as described for genus. Dentition. Teeth present on premaxilla, dentary, palatine, upper and lower pharyngobranchials; premaxilla and dentary as illustrated in figure 1 D and summarized in table 1. Toot crown length 17.9–26.4 % in tooth length. Premaxilla elongate, strongly arched in lateral view, with teeth arranged in two series: lateral and mesial. Lateral series in single row, divided into two groups: anterior, at anterior fourth of premaxilla, type 4, needle-like, without flange, closely spaced, increasing in size from anterior to posterior; and posterior, teeth with ventral attachment, recurved, with flange, as in teeth of mesial series, closely spaced, decreasing in size from anterior to posterior. Mesial series in single row; teeth with ventral attachment, recurved, with flange, widely spaced, decreasing in size from anterior to posterior; none developed as fang, largest tooth 14.9 –18.0% in premaxillary length. Base of first tooth at anterior fourth of premaxilla, anterior to level of anterior nostril, second tooth beside first tooth of lateral series, third below anterior nostril, and fourth at level of anterior margin of eye. Dentary elongate, moderately arched in lateral view; teeth arranged in two series: lateral and mesial. Lateral series in single row, divided into two groups: anterior, at anterior third of dentary, teeth type 4, needlelike, without flange, closely spaced, increasing in size from anterior to posterior; and posterior, teeth with ventral attachment, recurved, with flange, closely spaced, decreasing in size from anterior to posterior; none developed as fang, largest tooth 12.3–15.1 % in dentary length. Mesial series in single row; teeth with ventral attachment, recurved, with flange, decreasing in size from anterior to posterior. Base of first tooth at level of last needle-like tooth of lateral series, next teeth closely spaced to end of dentigerous area of dentary. Palatine teeth type 4, needle-like, without flange, in single row. Lower pharyngeal teeth type 4, needlelike, without flange, in small patches; upper pharyngeal teeth type 4, needle-like, without flange, in small patches. Gill rakers tooth-like, type 1, conical, slender, without flange, individually attached to bone, or in small patches of two; present on first, second, third and fourth arches; teeth absent in basihyal and basibranchials. Color. Skin covering body very thin, missing in most specimens, description based on LACM 30428 – 32 and holotype. Epidermis black or dark brown, thin and fragile, completely destroyed or restricted to small patches in all specimens examined; dermis thin, transparent, with widely spaced melanophores. Peritoneum transparent, with moderate concentration of melanophores. Orobranchial chamber pale, slightly dusky in roof and lateral sides of mouth, including opercle, skin below gill arch, membrane between branchiostegal rays and over basihyal and basibranchials; gill arches and filaments pale. Distribution. World-wide in the equatorial, tropical, and subtropical regions, except the western Pacific: in the Atlantic from 40 ° N to 31 ° S; in the western Indian from 24 ° S, 31 ° S; in the Pacific 33 ° N to 30 ° S (Fig. 6). Bathymetric distribution. Bathypelagic zone; more frequently recorded in depths between 1900 and 2500 m (mean 2239 m). A single record from above 1000 m (930 m); deepest record at 2750 m. : Published as part of Melo, Marcelo R. S., 2008, The genus Kali Lloyd (Chiasmodontidae: Teleostei) with description of new two species, and the revalidation of K. kerberti Weber, pp. 1-33 in Zootaxa 1747 on pages 19-22, DOI: 10.5281/zenodo.181658 : {"references": ["Parr, A. E. (1933) Deepsea Berycomorphi and Percomorphi from the waters around the Bahama and Bermuda islands. Scientific results of the third oceanographic expedition of the ' Pawnee' 1927. Bulletin of the Bingham Oceanographic Collection, 3, 1 - 51.", "Johnson, R. K. (1969) A review of the fish genus Kali (Perciformes: Chiasmodontidae). Copeia, 1969, 386 - 391.", "Johnson, R. K. & Cohen, D. M. (1974) Results of the research cruises of FRV Walther Herwig to South America. XXX. Revision of the chiasmodontid fish genera Dysalotus and Kali, with descriptions of two new species. Archiv fur Fischereiwissenschaft, 25, 13 - 46.", "Johnson, R. K. & Keene, M. J. (1986) Chiasmodontidae. In: Smith, M. M. & Heemstra, P. C. (Eds) Smith's sea fishes. Johannesburg, Macmillan South Africa, pp: 731 - 735.", "Johnson, R. K. & Keene, M. J. (1990) Chiasmodontidae. In: Quero, J. C., Hureau, J. C., Karrer, C., Post, A. & Saldanha, L. (Eds) Check - list of the fishes of the eastern tropical Atlantic. Paris, UNESCO, pp. 899 - 904.", "McEachran, J. D. & Sutton, T. (2003) Chiasmodontidae. In: Carpenter, K. E. (Ed) The living marine resources of the Western Central Atlantic. Volume 3: Bony fishes part 2 (Opistognathidae to Molidae). FAO species identification guide for fishery purposes and American Society of Ichthyologist and Herpetologists Special Publication No. 5. FAO, Rome, pp 1742 - 1743.", "Moore, J. A., Hartel, K. E., Craddock, J. E. & Galbraith, J. K. (2003) An annotated list of deepwater fishes from off the New England region, with new area records. Northeastern Naturalist, 10, 159 - 248.", "Hardy, J. D. (2005) Chiasmodontidae: swallowers. In: Richards W. J. (Ed.) Early stages of the Atlantic fishes - an identification guide to the Western Central North Atlantic. Taylor and Francis Group, Portland, pp. 1901 - 1915.", "Hardy, J. D. (2007) Early Stages of Fishes in the Western North Atlantic Ocean, (Davis Strait, Southern Greenland and Flemish Cap to Cape Hatteras). Northwestern Atlantic Fisheries Organization, Nova Scotia, 1696 pp."]}